The turnip - Brett, Jan, 1949- (G.P. Putnam's Sons, an imprint of Penguin Group (USA), 2015)
Badger Girl is delighted to find the biggest turnip she has ever seen growing in her vegetable garden, but when the time comes to harvest the giant root, she is unable to pull it up without help from family and friends.